Effects of Ultraviolet Radiation (UVA+UVB) and Copper on the Morphology, Ultrastructural Organization and Physiological Responses of the Red Alga Pterocladiella capillacea. (8th January 2015) - Schmidt, Éder C.; Kreusch, Marianne; Felix, Marthiellen R. de L.; Pereira, Debora T.; Costa, Giulia B.; Simioni, Carmen; Ouriques, Luciane C.; Farias‐Soares, Francine L.; Steiner, Neusa; Chow, Fungyi; Ramlov, Fernanda; Maraschin, Marcelo; et al.
Abstract The effect of ultraviolet (UV) radiation and copper (Cu) on apical segments of Pterocladiella capillacea was examined under two different conditions of radiation, PAR (control) and PAR+UVA+UVB (PAR+UVAB), and three copper concentrations, ranging from 0 (control) to 0.62, 1.25 and 2.50 μm. Algae were exposed in vitro to photosynthetically active radiation (PAR) at 70 μmol photons m−2 s−1, PAR + UVB at 0.35 W m−2 and PAR +UVA at 0.70 W m−2 during a 12‐h photocycle for 3 h each day for 7 days. The effects of radiation and copper on growth rates, content of photosynthetic pigments and photosynthetic performance were analyzed. In addition, samples were processed for light and transmission electron microscopy. The content of photosynthetic pigments decreased after exposure to radiation and Cu. Compared with PAR radiation and copper treatments modified the kinetics patterns of the photosynthesis/irradiance curve. The treatments also caused changes in the ultrastructure of cortical and subcortical cells, including increased cell wall thickness and accumulation of plastoglobuli, as well as changes in the organization of chloroplasts. The results indicate that the synergistic interaction between UV radiation and Cu in P. capillacea, led to the failure of protective mechanisms and causing more drastic changes and cellular imbalances.